Impact of a Pharmacist‐Led Antimicrobial Stewardship Program on Empiric Prescribing Appropriateness in the Emergency Department: A Retrospective Cohort Study - Ali A. Althubyani; Benito Fernandez Lopez; Lily G. Fechtmeyer; Daria K. Szczepanek; Melissa A. Catalano; Kyle Brown; Dana J. Holger (JACCP: JOURNAL OF THE AMERICAN COLLEGE OF CLINICAL PHARMACY, 2026)
ABSTRACT Background Inappropriate antimicrobial use in emergency departments (EDs) contributes significantly to antimicrobial resistance (AMR). Pharmacist‐led antimicrobial stewardship programs (ASPs) can potentially optimize antimicrobial prescribing and improve patient outcomes; however, their specific impact in the ED setting warrants further evaluation. Methods This retrospective cohort study evaluated adult patients receiving empiric antimicrobial therapy in the ED of a large, tertiary‐care, community teaching hospital in South Florida before (pre‐ASP) and after (post‐ASP) the implementation of a pharmacist‐led ASP. The primary outcome was the appropriateness of empiric antimicrobial therapy based on societal guidelines and local resistance patterns. Secondary outcomes included the use and appropriateness of antipseudomonal and anti‐Methicillin‐resistant Staph Aureus (MRSA) agents, as well as the appropriateness of vancomycin dosing. Logistic regression analyses identified predictors of inappropriate prescribing. Results A total of 324 patients (median age, 65 years; 53.4% female) were included, with 162 patients in both the pre‐ASP and post‐ASP groups. Appropriate empiric regimens did not differ significantly (49.4% vs. 53.7%, p = 0.44). There were significant reductions in unnecessary pseudomonal (54.9% vs. 35.2%; p < 0.001) and MRSA coverage (23.5% vs. 13.6%; p = 0.02), and vancomycin dosing appropriateness trended upward post‐ASP (52.6% vs. 77.3%; p = 0.06). The post‐ASP group demonstrated significant reductions in aztreonam (5.2% vs. 0.5%; p < 0.01), piperacillin/tazobactam (22.3% vs. 14.5%; p = 0.02), and vancomycin use (18.0% vs. 11.0%; p = 0.02), with increased ceftriaxone (17.5% vs. 33.0%; p < 0.001) and metronidazole prescribing (1.4% vs. 7.0%; p = 0.01). Independent predictors of inappropriate prescribing included home wound care (Adjusted odds ratio [aOR], 5.36; CI, 1.3–36.2), male sex (aOR, 1.72; CI, 1.1–2.8), and gastrointestinal infection (aOR, 2.67; CI, 1.1–6.7). Conclusion Although the overall rate of appropriate empiric therapy remained unchanged, the pharmacist‐led ASP was associated with reduced broad‐spectrum antimicrobial usage and enhanced vancomycin dosing accuracy. These findings suggest that pharmacists can help optimize ED antimicrobial use, although additional strategies are needed to improve overall appropriateness.